Does size matter? Bumblebee behaviour and the pollination of Cytisus scoparius L. (Fabaceae). - STOUT, JANE CATHERINE (EDP Sciences, 2000)
The effects of forager body size and floral display size on pollinator behaviour were assessed in a relatively specialised plant-pollinator system. Cytisus scoparius, which has structurally complex, nectarless flowers is pollinated by foraging bumblebees. Variations in bee body size affected the proportion of open flowers visited, the ability of bees to trigger the pollination mechanism of flowers and handling times on open flowers. Smaller bees handled flowers more successfully and efficiently than larger ones. Contrary to previous reports, all bees preferred to visit open flowers and possible explanations for this are discussed. Floral display size also affected behaviour as bees visited more flowers per plant on larger plants, but visited a lower proportion of the available flowers. There was no interaction between body size and floral display size, suggesting that bees of all sizes respond in a similar manner to variations in floral display sizes. The potential impacts of variations in bumblebee behaviour on plant reproductive success are discussed.
PUBLISHED
Keywords: foraging behaviour; pollination; body size; floral display size; Bombus spp.